Artificial Intelligence pada Google Maps berdasarkan Hak Kekayaan Intelektual: Artificial Intelligence On Google Maps Based On Intellectual Property Rights - Fauzan Akmal; Aline Gratika (Faculty of Law, Universitas Trisakti, 2024)
Google Maps is an example of a computer program based on Artificial Intelligence. Howerver, until now, there are no explicit regulations, especially in Intellectual Property Law in Indonesia, that govern it. The issue in this research is How are the intellectual property rights of Artificial Intelligence on Google Maps?. Therefore, this research will analyze Artificial Intelligence on Google Maps based on Intellectual Property Rights. This research uses normative research methods that utilize secondary data and also primary data only as supporting data, the nature of this research is descriptive and conclusions are drawn using deductive methods. The results of this research are Artificial Intelligence is the result of human thought processes that become assets and generate rights that need to be protected, and based on intellectual property rights, Artificial Intelligence can be said to be a computer program where there are only 2 legal aspects regulating it, namely copyright and patents, the scope of which depends on the final form of the Artificial Intelligence itself. Based on the analysis of intellectual property rights on Google Maps as Artificial Intelligence, from its operation,it can be said to fall within the scope of patents.